Engineering ligands on the Au center: discovering broadly applicable gold catalysis with high turnover numbers - Inamdar, Suleman M.; Patil, Nitin T. (Organic Chemistry Frontiers, 2015)
The research groups of Hammond/Xu and Zhang report the discovery of new ligands for gold catalysis. With these ligands, gold catalyzed reactions have been reported for a broader range of substrates with very high TONs at a level that can match the needs of large-scale applications.